Large intrahepatic duodenal duplication cyst with a preduodenal portal vein - Yudai Tsuruno; Hiroaki Fukuzawa; Mitsumasa Okamoto; Harunori Miyauchi; Yumiko Nakai (Elsevier, 2022)
Duodenal duplication cyst is rarely located inside the liver. We present an extremely rare case of a 12-year-old girl with a large intrahepatic duodenal duplication cyst and a preduodenal portal vein. She was incidentally diagnosed with a large liver cyst (6.5 × 6.1 × 3.6 cm) containing air and fluid with a preduodenal portal vein after a systemic computed tomography scan for suspected internal injuries because of a traffic accident. The upper gastrointestinal series revealed that the cyst communicated with the duodenal bulb via a wide stalk. Upper gastrointestinal endoscopy revealed a large entry hole to the cyst at the duodenal bulb. Biopsy of the inner surface of the cyst revealed that the alimentary mucosa resembled that of the duodenum. She had no symptoms; therefore, continued observation was recommended as the sole management option. This is the third case of this extremely rare condition reported in the literature. This report describes and compares the common features of the three cases.